Evaluation of the delayed hydrogen cracking behavior and the hydrogen diffusion coefficient for different microstructures of the Zr-2.5%Nb alloy - Gomez, Adrian Guillermo; Páez Ponce, Jose; Grosse, M.; Soria, Sergio Raul; Condo, Adriana Maria; Flores, Alejandra; Schulz, Michael; Vizcaino, Pablo; Santisteban, Javier Roberto (Elsevier Science, 2023)
Fil: Gomez, Adrian Guillermo. Comisión Nacional de Energía Atómica. Gerencia de Área de Aplicaciones de la Tecnología Nuclear. Gerencia Ciclo del Combustible Nuclear. Laboratorio de Materia de la Fábrica de Aleaciones Especiales; Argentina